Safety and human error in engineering systems - Dhillon, B. S. (CRC, 2013)
This book combines coverage of safety and human factors in engineering into a single volume, eliminating the need to consult many different and diverse sources to obtain desired information. It discusses mathematical concepts necessary to understanding material presented in subsequent chapters. The author describes the methods that can be used to perform various types of safety and human error analysis in engineering systems. The book contains examples along with their solutions and at the end of each chapter are numerous problems to test reader comprehension.